2008
DOI: 10.1345/aph.1k369
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Cerebrovascular Events Associated with Antidepressant Use in Patients with Depression: A Population-Based, Nested Case-Control Study

Abstract: Current users of antidepressants may be at increased risk of a CVE. Clinicians should consider the relationship of antidepressants with the occurrence of CVEs when determining the risk-benefit profile of pharmacologic treatment in patients with depression, particularly those with existing risk factors for a CVE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 35 publications
1
54
0
1
Order By: Relevance
“…Conversely, it has been proposed that SSRIs stimulate vasoconstriction via serotonin receptors on vascular smooth muscle (Wu et al, 2011). Regardless of these seemingly contradictory effects on perfusion, these agents have been extensively associated with both cardiovascular disease and cerebrovascular events (Chen et al, 2008;Smoller et al, 2009;Weeke et al, 2012;Whang et al, 2009;Wu et al, 2011). The two studies that specifically examined the effect of SSRIs on WMHs both found an increase in WMHs among SSRI-treated patients, but only one demonstrated a statistically significant relationship (Grool et al, 2013;Steffens et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, it has been proposed that SSRIs stimulate vasoconstriction via serotonin receptors on vascular smooth muscle (Wu et al, 2011). Regardless of these seemingly contradictory effects on perfusion, these agents have been extensively associated with both cardiovascular disease and cerebrovascular events (Chen et al, 2008;Smoller et al, 2009;Weeke et al, 2012;Whang et al, 2009;Wu et al, 2011). The two studies that specifically examined the effect of SSRIs on WMHs both found an increase in WMHs among SSRI-treated patients, but only one demonstrated a statistically significant relationship (Grool et al, 2013;Steffens et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, evidence from observational studies suggested an increased risk of stroke in relation to treatment with antidepressants. 39,40 However, these findings should be treated with cautions because of the possible confounding by indication (depression severity). In other words, patients treated with antidepressants are more likely to have severe depressive symptoms, and the observed increased risk of stroke may be attributable to depression severity rather than the antidepressant use.…”
Section: Dong Et Al Depression and Risk Of Stroke 33mentioning
confidence: 99%
“…Two previous studies showed an increased risk of ischemic stroke in current SSRI users. 16,24 This increased risk could be explained by a different biological mechanism, which postulates that serotonin induces vasoconstriction of large vessel, and may lead to thromboembolic ischemic stroke in the presence of atherosclerosis. 52 However, in our study, we focused on silent ischemic vascular lesions, involving the small cerebral arteries, which are typically not caused by thromboembolic events.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] SSRIs block the reuptake of serotonin by platelets and decrease serotonin platelet concentration, which may lead to impaired aggregation and prolonged bleeding times. [10][11][12][13][14] SSRIs have, therefore, extensively been studied in relation to intracerebral hemorrhages, [15][16][17][18][19][20][21][22] and a recent meta-analysis of controlled observational studies showed an increased risk of intracerebral hemorrhages in SSRI users compared with nonusers. 23 In addition, via the same pathophysiological pathway of reducing platelet aggregation, antidepressants with a high inhibition for serotonin reuptake may also reduce the risk of ischemic stroke, although to date this hypothesis is scarcely supported by literature.…”
Section: See Related Article P 1917mentioning
confidence: 99%
See 1 more Smart Citation